High luminous efficiency of a phosphor-in-glass plate by optimization of the glass and phosphor content for high-power LED applications. (1st May 2023) - Lee, In-Jae; Noh, Hyun Sung; Elayappan, Vijayakumar; Kwon, Dawool; Kim, Young Hoon; Sun, Min Kyu; Kim, Seoung Eon; Lee, Haigun
Abstract: Generally, white light-emitting diodes (LEDs) are fabricated by combining blue LED chips with yellow phosphors. When fabricating white LEDs, the phosphor is typically mixed with an organic resin and applied to the LED chips as a paste. A phosphor-in-glass (PiG) plate can alternatively be used to address the poor high-temperature reliability of the paste method. However, because pores form in the PiG plate during the sintering process, this method results in a loss of optical efficiency. Accordingly, we aimed to improve the fluidity of glass and light efficiency by optimizing the sintering temperature of the glass powder and the phosphor content respectively for reducing internal porosity in the PiG. In this study, glass powder was sintered at different temperatures to produce glass plates, while also varying the phosphor content to fabricate PiG plates. The optimal light characteristics were realized with a glass sintering temperature of 640 °C and a phosphor content of 20 wt%.